The Effect of Yamamoto New Scalp Acupuncture Therapy on Lowering The Blood Pressure of Hypertension Patients At A Primary Care Service Family Medicine Acupuncture Clinic ''XYZ'' Jakarta - Yuliawati Kusumaningrum; Mayang Wulandari; Ikhwan Abdullah; Chantika Mahadini (Syntax Corporation, 2022)
Hypertension can hinder the development of social and economic stability and can become a major threat to the structure of healthcare services. The management of hypertension cases in primary care can be performed through a family medicine approach by taking into account the potential of the family as the supporting resource and/or obstacles to the successful management of hypertension patients. This can be performed with acupuncture methods, one of which is the Yamamoto New Scalp Acupuncture (YNSA) method. Objective: To determine the effect of acupuncture therapy using YNSA method on lowering the blood pressure of patients with hypertension at the Primary Care Service Family Medicine Clinic